Efeito da suplementação da vitamina A, sôbre o desenvolvimento e produção de leite de novilhas - Américo Garcia, José; Milagres, João Camilo; Ribeiro Gomes, Fábio (Revista Ceres, 2025)
The experiment was conducted during 444 days at the Universidade Federal de Viçosa with 20 Holstein-Zebu crossbred heifers. The heifers averaged 14 months of age and 256 kilos in weight at the beginning of the experiment.